Uji Organoleptik Nugget Ikan Kembung dengan Penambahan Rumput Laut (Eucheuma cottonii) - Danna Aditry Wijaya; Damiati Damiati; Ida Ayu Putu Hemy Ekayani (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to describe: 1) Formulation of mackerel fish nuggets with the addition of seaweed (Eucheuma cottonii); 2) to detemine the level of panelists’ preference for the resulting product. This study uses a quantitative method with an experimental approach. Data colletion uses an observation method by distributing preference test sheet to the public (consumers). Then analyzed using quantitative descriptive. Research results: 1) Formulation using 350 gr mackerel surimi, 70 gr seaweed (Eucheuma cottonii), 60 gr eggs, 100 gr wheat flour, 15 gr garlic, 30 gr shallots, 2,5 gr ground pepper, 10 gr salt, 5 gr sugar; 2) The preference test results indicated that the inner color (4,38), outer color (4,58), solid inner texture (4,44), crispy outer texture (4,26), aroma (4,36), natural taste (4,48), and shape (4,6) were in the very liked category, while the chewy inner texture (4,08) and savory taste of the spices (4,14) were in the liked category. Overall, mackerel nuggets with the addition of seaweed (Eucheuma cottonii) were categorized as very liked and had the potential to become an innovative product that was accepted by the the general public.